Les agents révolutionnaires français à Barcelone au printemps 1821 - Laurent Nagy (Mélanges de la Casa de Velázquez)
In the spring of 1821, the exaltados of Barcelona were spectators of the struggle taking place in the south of the Italian peninsula between the Neapolitan carbonari, their cousins in freedom, and the Austrian army commissioned by the powers making up the Holy Alliance to put them down. When, in mid-April, the first refugees disembarked on the quays of Barcelona, the city became a strategic point in the cartography of the zones of conflict between the monarchies forming the Holy Alliance and the armed supporters of the Constitution. Situated between Paris, Naples and Madrid, the city was soon seen as an inevitable crossroads for subversive movements. While attracting the attention of the diplomatic cabinets of the continent, the Catalan port became a hotbed of political intrigue whose real stakes went far beyond the province’s borders. The aim here is to analyse the actions of French revolutionary agents in Barcelona during the spring of 1821 and to use this micro-history to look back at the interference of these expatriates in local politics. This small-scale article is part of a vast research on the political transfers between the kingdom of Louis XVIII and that of Ferdinand VII during the Trienio liberal.